Notes from the Director, National Heart, Lung, and Blood Institute: transitions - Nabel, Elizabeth G. (American Society of Hematology, 2009)
During this time of transition in the federal government and the National Institutes of Health, I write to assure the Blood community of the National Heart, Lung, and Blood Institute's (NHLBI) commitment to new and established investigators as outlined in the NHLBI Strategic Plan. This perspective discusses the NHLBI budget for the fiscal year 2009 and new policies for funding early stage investigators and revised grant applications.